Sharia – Compliant Instruments as Innovative Financing for Transportation Infrastructure Development in Indonesia - Dikun, Suyono; Lamari, Fiona; Rarasati, Ayomi D.; Rahman, Herawati Z.; Anggraeni, Devy (CSID Journal of Infrastructure Development, 2015)
Indonesia’s transportation development in the next 5 years is projected to be accelerated to cope with the deficit and gap that had been built up over the last two decades. A study conducted by Bappenas and JICA for the National Mid-Term Development Plan (RPJMN) 2015-2019 projected the magnitude of investment needed for the transport sector in sums up to IDR 2,500 trillion or around IDR 500 trillion per year. The state budget (APBN) had been and will always be insufficient to finance the total needs for transport investment. The innovative financing in transport development becomes very urgent given the tight fiscal allocation of Indonesia’s state budget, which is not adequate in financing infrastructure development. Indonesia needs to be innovative to find other sources of funds to finance transportation development. There are two streams: (1) to create a financing scheme based on the state budget, such as a Performance-Based Annuity Scheme (PBAS), infrastructure bonds, and shariah-based bonds (Sukuk) and (2) to create a non-state budget financing scheme to utiize domestic funds that are available domestically. The aim of this paper is to explore the possibility of Shariah-Compliant financing as a financing option for Indonesia’s infrastructure development. The methodology consists of estimating the infrastructure funding requirement in Indonesia, an understanding of Shariah-Compliant instruments in the global context, and lessons learned from other countries who who have applied Shariah-Compliant instruments for their infrastructure projects.